A SF5 Derivative of Triphenylphosphine as an Electron-Poor Ligand Precursor for Rh and Ir Complexes - Maria Talavera; Silke Hinze; Thomas Braun; Reik Laubenstein; Roy Herrmann (Molecules, 2020)
The synthesis of the triarylphosphine, P(p-C6H4SF5)3 containing a SF5 group, has been achieved. The experimental and theoretical studies showed that P(p-C6H4SF5)3 is a weaker σ-donor when compared with other substituted triarylphosphines, which is consistent with the electron-withdrawing effect of the SF5 moiety. The studies also revealed a moderate air stability of the phosphine. The σ-donor capabilities of P(p-C6H4SF5)3 were estimated from the phosphorus-selenium coupling constant in SeP(p-C6H4SF5)3 and by DFT calculations. The behavior of P(p-C6H4SF5)3 as ligand has been investigated by the synthesis of the iridium and rhodium complexes [MCl(COD){P(p-C6H4SF5)3}], [MCl(CO)2{P(p-C6H4SF5)3}2] (M = Ir, Rh), or [Rh(µ-Cl)(COE){P(p-C6H4SF5)3}]2, and the molecular structures of [IrCl(COD){P(p-C6H4SF5)3}] and [Rh(µ-Cl)(COE){P(p-C6H4SF5)3}]2 were determined by single X-ray diffraction. The structures revealed a slightly larger cone angle for P(p-C6H4SF5)3 when compared to other para-substituted triarylphosphines.